The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/bjs.4452
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of laparoscopic repair for perforated peptic ulcer

Abstract: Laparoscopic repair of perforated peptic ulcer is a safe emergency procedure in routine clinical practice for patients with perforated pyloroduodenal ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
2
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 16 publications
6
69
2
8
Order By: Relevance
“…53,54 In our study pre pyloric perforation was commonest site while other investigators had reported first part of duodenum as common site for ulcer location. 15,51,55 However all share the common pathophysiology with acid hyper secretion and high prevalence of helicobacter pylori infection. 56,57 In our study Modified Graham's patch with a pedicle omental patch repair was done in all cases with routine eradication of helicobactor pylori infection to avoid recurrences and re-perforation.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 In our study pre pyloric perforation was commonest site while other investigators had reported first part of duodenum as common site for ulcer location. 15,51,55 However all share the common pathophysiology with acid hyper secretion and high prevalence of helicobacter pylori infection. 56,57 In our study Modified Graham's patch with a pedicle omental patch repair was done in all cases with routine eradication of helicobactor pylori infection to avoid recurrences and re-perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Artık günümüzde konvansiyonel laparotomi yerine endoskopik ve laparoskopik yardımcı yöntemler tedavi aşamasında artan oranlarda kullanılmaktadır. [2,3] Tedavi seçeneklerinin çeşitli olması ve acil karar verme zorunluluğu nedeniyle gö-rüntülemede yanıtlanması gereken temel soru perforasyonun yeri ve nedeninin ortaya konmasıdır. Doğru tedavinin planlanması için perforasyonun varlığı, yeri ve nedeni belirlenmelidir.…”
Section: Resultsunclassified
“…Minimal access surgery was associated with a significantly lower wound infection, reduced postoperative pain and analgesic consumption, a lower mortality rate and a shorter hospital stay [13][14][15][16][18][19][20]. Laparoscopy is also preferred when managing patients with acute abdomen and no radiographic changes [21]. However, this technique has a longer operating time and is not recommended for hypotensive patients, patients with a coexisting medical disease or previous upper abdominal surgery, in critical condition and in the presence of some technical difculties or large ulcers [13][14][15][16][18][19][20].…”
Section: Discussionmentioning
confidence: 99%